β-Sitosterol Reduces the Expression of Chemotactic Cytokine Genes in Cystic Fibrosis Bronchial Epithelial Cells - Lampronti, Ilaria; Dechecchi, Maria C.; Rimessi, Alessandro; Bezzerri, Valentino; Nicolis, Elena; Guerrini, Alessandra; Tacchini, Massimo; Tamanini, Anna; Munari, Silvia; D’Aversa, Elisabetta; Santangelo, Alessandra; Lippi, Giuseppe; et al. (Frontiers in Pharmacology, 2017)
Extracts from Nigella arvensis L. seeds, which are widely used as anti-inflammatory remedies in traditional medicine of Northern Africa, were able to inhibit the expression of the pro-inflammatory neutrophil chemokine Interleukin (IL)-8 in Cystic Fibrosis (CF) bronchial epithelial IB3-1 cells exposed to the Gram-negative bacterium Pseudomonas aeruginosa. The chemical composition of the extracts led to the identification of three major components, β-sitosterol, stigmasterol and campesterol, which are the most abundant phytosterols, cholesterol-like molecules, usually found in plants. β-sitosterol (BSS) was the only compound that significantly reproduced the inhibition of the P. aeruginosa-dependent expression of IL-8 at nanomolar concentrations. BSS was tested in CF airway epithelial CuFi-1 cells infected with P. aeruginosa. BSS (100 nM), showed a significant and consistent inhibitory activity on expression of the P.aeruginosa-stimulated expression chemokines IL-8, GRO-α GRO-β,     in the recruitment οinflamed lungs. Preliminary mechanistic analysis showed that BSS partially inhibits the P. aeruginosa-dependent activation of Protein Kinase C isoform alpha, which is known to be involved in the transmembrane signaling activating IL-8 gene expression in bronchial epithelial cells. These data indicate BSS as a promising molecule to control excessive lung inflammation in CF patients.